Electrochemical behaviour of isatin at a glassy carbon electrode - Diculescu, Victor C. (2006)
The electrochemical behavior of isatin - a molecule with a broad range of applications in synthetic, biological and clinical activity - has been investigated over a wide pH range at a glassy carbon electrode (GCE) using cyclic, square wave and differential pulse voltammetry. The oxidation of isatin is an irreversible process, pH dependent and occurs with the formation of a main oxidation product that strongly adsorbs on the electrode surface. The reduction of isatin is also a pH dependent irreversible process. Cyclic voltammograms show two consecutive charge transfer reactions. The diffusion coefficient of isatin was calculated in pH 7.0 phosphate buffer to be D0 = 4.9 × 10-7 cm2 s-1. The limit of detection obtained in a solution of pH 7.0 phosphate buffer was LOD = 0.194 [mu]M, based on three times the noise level.